1856-1857 N.C. Sess. Laws 22, Pub. Laws, ch. 24, § 1. - (:unkn) unknown (General Publisher, 1856)
[T]he true intent and meaning of the 95th section of the 34th chapter of the Revised Code was and is hereby declared to be to prevent fire hunting for deer with a gun or guns in the night time, and nothing more.
--
Keywords: HUNTING REGULATION